2018
DOI: 10.1186/s12906-018-2181-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with utilization of herbal medicines among outpatients in primary health centers in Cambodia

Abstract: BackgroundTraditional, complementary and alternative medicine (TCAM) is seen as a way to provide healthcare in both developed and developing countries across the world. In Cambodia, there is a long tradition of using TCAM. However, scant studies have been conducted on the extent of Cambodian TCAM use and how it interacts with allopathic health care to date. In this study, we examined the prevalence of and factors associated with utilization of herbal medicines among patients with chronic diseases in primary he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 35 publications
3
19
2
1
Order By: Relevance
“…Several studies2022 found that being a woman and younger or older age were associated with herbal medicine use, while in this study only in bivariate analysis women had a higher prevalence of herbal medicine use than men had, and no age differences were found. This study found that having completed primary education increased the odds for herbal medicine use, while in a community survey in Turkey22 higher education was positively and among chronic disease patients in Cambodia16 was negatively associated with herbal medicine use. Consistent with some studies on traditional and complementary medicine utilization,17,19 this study found that rural residence increased the odds for herbal medicine use.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Several studies2022 found that being a woman and younger or older age were associated with herbal medicine use, while in this study only in bivariate analysis women had a higher prevalence of herbal medicine use than men had, and no age differences were found. This study found that having completed primary education increased the odds for herbal medicine use, while in a community survey in Turkey22 higher education was positively and among chronic disease patients in Cambodia16 was negatively associated with herbal medicine use. Consistent with some studies on traditional and complementary medicine utilization,17,19 this study found that rural residence increased the odds for herbal medicine use.…”
Section: Discussionmentioning
confidence: 63%
“…Findings show a high prevalence of past 12-month herbal medicine use (35.9%) among chronic disease patients in Thailand, higher than in Lao PDR (21.3%)17 and Malaysia (24.9%), and lower than in Vietnam (43.6%),20 Cambodia (44.5%),16 and Myanmar (53.2%) 19. This high prevalence of past 12 month herbal medicine use among chronic disease patients in Thailand confirms findings of lifetime, 12-month and past 3-month herbal medicine use in different study populations in Thailand: hospital patients 28.6%,7 gynaecologic cancer patients 27.0%,10 cancer patients treated with radiotherapy past-12-month use of 31.1%,11 diabetes patients past 3-month use of 20.1%,12 and 42% taking herbal medicine together with modern medication,32 chronic kidney disease patients past 12-month use of 27.3%,13 and among persons living with HIV lifetime use of 32% 14.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The use of medicinal plants for health treatment, cure or even disease prevention can be considered one of the oldest forms of medical practice [1]. Even today, the use of medicinal plants or other alternative practices can be the only therapeutic resources for many communities and ethnic groups, especially in developing countries [2][3][4].…”
Section: Introductionmentioning
confidence: 99%